Interactivity gratifications - Adwoa Sikayena Amankwah; Blessing Mbatha (Communicare)
The study explored how the interactive attributes of new media technologies influence the gratification-seeking behaviour of millennials. Using a mixed methods approach, it employed a survey and focus group interviews to collect data from university students. From a population of 2 400 university students from the Political Science Department of a renowned public university in Ghana, 400 students were systematically sampled for the survey, while 40 students were purposively selected for focus group discussions. The findings indicate that the interactive features of the technologies produced emerging social and psychological gratifications in millennials by projecting them as purposeful, and active in deploying symmetric political communication repertoires. The practical implication of this is that political leaders need to invigorate their electoral communication repertoires both in substance and in depth by deploying the heuristic attributes of the new technologies to facilitate the awakening of visceral responses in millennials and get them to engage in e-politics.